O esporte no contexto escolar : organização e prática extracurricular - Silva Junior, Edesio Rodrigues da (2022)
Sport is a sociocultural phenomenon that is becoming present in people's lives, with a mobilization potential that involves several environments, possibilities, and meanings. It is institutionally recognized as a right for everyone. In the school context it is the main content of physical education classes and extracurricular activities. However, how is sport being organized at school? In this context, as the central theme of the research, we aimed to understand how sport has been discussed and organized at school in extracurricular activities. In general, this is a qualitative and descriptive study. The dissertation is organized in chapters that deal with the theme. In the first chapter we will present an panorama study of the publications that address sport in the school context. The purpose of this text is to identify how sport within the school context has been discussed in Brazilian journals over the years, from 1990 to 2019. We found 246 articles that address the theme. The data reveal an increase in publications over the years, with the last decade concentrating most of the publications. The articles were categorized as: a) addressing sport as a regular content of school physical education (n=161); b) addressing sport in extracurricular activities at school (n=85). In the second chapter, we intend at evidencing, through the statements of managers (direction and coordination) how sport is organized, in an extracurricular context, in schools that stand out in the Mato Grosso School Games. For the selection of the schools participating in the research, a search was conducted of the bulletins of the Mato Grosso school games was carried out of the institutions that obtained a higher incidence of participation in this competition in the 2016, 2017, and 2019 editions. The data collection was carried out through interviews, via video call application, with semi-structured questions that meet the objectives of the work. The results revealed that extracurricular sport in school still has the predominance of informality. The teachers/coaches were pointed out as fundamental for the development of the sport projects. The sport was recognized by the managers as an important instrument in the formation of the students. It is expected that this dissertation may bring new discussions and deepening of the theme, as well as notes and propositions for school sport.